The need to transition from paper to electronic instructions for use for diabetes devices - Cindy N. Ho; Alessandra T. Ayers; Lutz Heinemann; David C. Klonoff (npj Digital Medicine)
Regulatory agencies, such as the European Commission and the U.S. Food and Drug Administration, are now permitting electronic instructions for use (eIFUs) to be distributed alongside paper instructions for use (IFUs) for medical devices. However, challenges remain regarding the implementation of eIFUs to replace paper IFUs in the era of digital health. Our work examines regulatory, consumer, and environmental factors that influence the transition from paper-based IFUs to eIFUs for wearable diabetes devices.